The attractiveness of the Thai tourist industry - Narisara Rochananond; Tang, John C.S.; Oudheusden, Dirk L. van; Huynh, Ngoc Phien; Government of Belgium (Bangkok : Asian Institute of Technology, 1988)
Tourism is a large and growing industry. In recent years, earnings from tourists have become the single largest source of foreign exchange for THAILAND. This research is an attempt to assess the attractiveness of THAILAND as a tourist destination compared to other selected countries. Thirty two countries, where tourism is an important sector, are considered. Eight major attributes were identified to be important factors affecting tourism. Results indicate that for all groups, the most important factor affecting tourist attractiveness is 'Natural Beauty & Climate'. 'Accessibility of the Country' is found to be relatively not a very important for all three groups of respondents in the choice of tourist destination. THAILAND was ranked either first or second by respondents in the three groups. THAILAND does possess very good rankings of important attributes that tourist look for and this certainly explained why THAILAND is consistently ranked at the top. Countries were also grouped into c lusters by using KMEANS clustering method in order to assess competitiveness. Based on the results of the cluster analysis, THAILAND cannot be clustered with any of the countries. THAILAND appears to be 'unique ' in terms of attractiveness: this means that it is difficult in this study , to make any conclusions regarding competition for policy planner in the tourism industry. From both the ranking results as well as those obtained from cluster analysis, the U.S. is found to be very closely ranked as well as very competitive compared to THAILAND. Policy makers in THAILAND should therefore pay close attention to some of the attributes that are favored by all respondents and in which the U.S. is much better ranked.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Engineering and Technology
Thesis (M.Sc.) - Asian Institute of Technology, 1988
Keywords: Tourist trade -- Thailand